Middleware 2012 ACM/IFIP/USENIX 13th International Middleware Conference, Montreal, Canada, December 3-7, 2012. Proceedings - Narasimhan, Priya; Triantafillou, Peter (Programming and Software Engineering, 2012)
This book constitutes the refereed proceedings of the ACM/IFIP/USENIX 13th International Middleware Conference, held in Montreal, Canada, in December 2012. The 24 revised full papers presented were carefully reviewed and selected from 125 submissions. The papers are organized in topical sections on mobile middleware; tracing and diagnosis; architecture and performance; publish/subscribe middleware; and big-data and cloud computing; availability, security and privacy.